Level Penambahan Emulsifier Natrium Sitrat dan Dinatrium Fosfat terhadap Kadar Protein, pH dan Kadar Laktosa Keju Olahan: Level of Addition of Sodium Citrate and Disodium Phosphate Emulsifiers to Protein Content, pH and Lactose Content of Processed Cheese - Mudawaroch, Roisu Eny (Jurnal Riset Agribisnis dan Peternakan, 2024)
Processed cheese is made by adding an emulsifier. Emulsifiers commonly used come from sodium salts, namely sodium citrate and disodium phosphate. The purpose of this study was to determine the level of addition of sodium citrate and disodium phosphate emulsifiers to protein levels, pH and lactose levels. Research method using complete randomized design (RAL) with 5 treatments, namely E0= 0%; E1= 1%; E2=25, E3=3% and E4=4%, and repeated 4 times. The result of the study was that the addition of emulsifiers had a real effect on protein levels. Protein value E0= 31.57; E1= 33.35; E2=33.8; E3=34.87 and E4=31.67. The addition of sodium citrate and disodium phosphate emulsifiers has a very significant effect on increasing the pH value. The highest pH value at E3 = 5.56±0.04. The addition of sodium citrate and disodium phosphate emulsifiers has a significant effect on lactose levels. Emulsifiers added 3% give the highest lactose content of 3.08 percent. Conclusion The addition of sodium citrate and disodium phosphate emulsifiers produces a very significant effect on protein levels and latous levels, while on pH values a real effect. The addition of sodium citrate and disodium phosphate as much as 3% gives the highest value on protein content, pH and lactose levels. In making processed cheese using the basic ingredients of mozzarela cheese as much as 80% and cheddar cheese as much as 20%, you should use emulsifier as much as 3%.